Workbook for step-by-step medical coding - Buck, Carol J. (Elsevier Saunders, 2015)
Strengthen your ability to code accurately and obtain optimal reimbursement for medical services! Corresponding to the chapters in Carol J. Buck's Step-by-Step Medical Coding, 2015 Edition, this workbook offers review and practice with more than 1,500 questions and terminology exercises (with odd-numbered answers provided), and includes a complete review for ICD-10-CM and ICD-9-CM. It also includes over 90 original source documents to familiarize you with the reports you will encounter in practice